2018
DOI: 10.1159/000490387
|View full text |Cite
|
Sign up to set email alerts
|

Management of Diverticular Hemorrhage: Catching That Culprit Diverticulum Red-Handed!

Abstract: Background/Summary: Acute colonic diverticular hemorrhage (CDH) represents a significant challenge for gastroenterologists. There are some clinical problems in the diagnosis, treatment, and prevention of CDH. CDH is the most common cause of overt lower gastrointestinal bleeding in adults in Eastern and Western countries. Moreover, CDH imposes significant economic and clinical burdens on the health care system. Colonoscopy is recommended as a useful diagnostic tool for CDH after bowel preparation. Colonoscopy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Endoscopic techniques such as thermocoagulation, epinephrine injection, banding, endoscopic detachable snare ligation, topical hemostatic agents, hemoclipping, and over-the-scope clip have recently been proposed for colonic diverticular bleeding. 12 , 24 However, no consensus exists due to inherent limitations of colonoscope reinsertion and the high cost associated with each technique. In a meta-analysis of cumulative evidence, Nagata et al demonstrated that endoscopic ligation therapy was more effective compared with hemoclipping in reducing short- and long-term recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic techniques such as thermocoagulation, epinephrine injection, banding, endoscopic detachable snare ligation, topical hemostatic agents, hemoclipping, and over-the-scope clip have recently been proposed for colonic diverticular bleeding. 12 , 24 However, no consensus exists due to inherent limitations of colonoscope reinsertion and the high cost associated with each technique. In a meta-analysis of cumulative evidence, Nagata et al demonstrated that endoscopic ligation therapy was more effective compared with hemoclipping in reducing short- and long-term recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have investigated LGB, the number of studies researching CDB is small. However, CDB is the most common cause of LGB 17 . Thus, investigating the efficacy of urgent colonoscopy for the rate of CDB‐related unfavorable event, including in‐hospital death, and clinical factors that affect the clinical course of CDB is necessary to treat LGB.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no previous study had reported an association between urgent colonoscopy and in‐hospital death. Although CDB typically has a relatively good prognosis, 4,5,17 some cases have a fatal course. However, the rate of mortality in CDB is very low.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of lower GI bleeding can be summarized to diverticulosis (which is the protrusion of the colon wall at the site of penetrating vessels, and by time the mucosa lining the vessel can be injured and ruptured leading to bleeding), infectious colitis, ischemic colitis, angiodysplasia, inflammatory bowel disease, colon cancer, hemorrhoids, anal fissures, rectal varices, dieulafoy lesion, radiation-induced damage following cancer treatment, and post-surgical [5]. According to the UCLA-Center for Ulcer Research and Education (CURE) database, discussing frequencies of different etiologies, excluding upper GI sources, diverticulosis is still the most common cause of 30 % of lower GI bleeding cases that require hospitalization, the second most common cause is hemorrhoids, another causes frequencies is increasing greatly as ischemic colitis and post-polypectomy bleeding; this increase is due to the increasing use of anti-platelet/anticoagulant [21][22][23][24].…”
Section: Causes Of Lower Gi Bleedingmentioning
confidence: 99%
“…Occult, moderate, and massive bleeding are three categories of lower GI bleeding [21,22]. Occult bleeding in lower GI present in patients at any age.…”
Section: Causes Of Lower Gi Bleedingmentioning
confidence: 99%